Antiseizure Medication in the Setting of Systemic Illness: A Focused Review - Menon, Bindu; Menon, Medha; Yadav, Praveen Kumar; Bardhan, Mainak (International Journal of Epilepsy, 2025)
Epilepsy is a common neurological disorder, and managing seizures can be challenging when other systemic illnesses are present, as these can affect the choice of antiseizure medication (ASM). Various comorbidities, such as cardiovascular disorders, liver and kidney impairment, psychiatric conditions, porphyria, and thyroid dysfunction, can significantly influence the pharmacokinetics and pharmacodynamics of ASMs. This requires careful selection of suitable ASMs based on their safety profiles and potential for drug interactions. Traditional ASMs such as phenytoin, carbamazepine, and valproate should be taken cautiously in individuals with cardiovascular disorders because of the possibility of side effects. Conversely, newer medications like lamotrigine and lacosamide (LCM) may offer safer alternatives. Levetiracetam and LCM are examples of medications with minimal hepatic metabolism, which are recommended since hepatic dysfunction can impact the binding potential of ASMs and result in toxicity. Furthermore, drugs that are mostly eliminated by the kidneys may take longer to be eliminated due to renal impairment, necessitating dose adjustments or the consideration of alternate therapies. ASMs can also affect psychiatric conditions; some medications may provide mood-stabilizing or antidepressant effects, while others may worsen psychiatric symptoms. Certain ASMs can trigger porphyria or disrupt thyroid function, necessitating careful monitoring and appropriate selection of treatments. This review offers a comprehensive overview of considerations and recommendations for the use of ASMs in various systemic illnesses, highlighting the need for a sophisticated strategy to maximize managing seizures while reducing side effects and medication interactions.
Keywords: epilepsy; antiseizure medications (ASMs); systemic illnesses; pharmacokinetics; safety profiles